Vacuum Field Photonic Trap for Excitons. Issue 7 (27th May 2021) - Gurioli, Massimo
Abstract: The spectral and spatial dependence of the resonant Lamb shift of an exciton inside a photonic vacuum field landscape is considered to predict an optical dipole potential generated via virtual photons quantum fluctuations. This trapping potential can be exploited for exciton self‐positioning in electric field hotspots at the nanoscale in view of quantum electrodynamics effects. By non Hermitian decomposition of the electromagnetic Green tensor in terms of quasi normal modes, the resonant part of the Lamb shift is expressed as Fano profile strictly interlinked to the Purcell enhancement of the exciton radiative lifetime. This approach explains how to tailor the depth of the vacuum photonic potential in several possible scenarios. Abstract : Exciton localization at electric field antinodes of a photonic mode is necessary for manipulating the quantum sources in solid state. This work demonstrates a quite promising way of self‐trapping the exciton via the radiative Lamb shift, predicting an optical dipole potential generated via virtual photons quantum fluctuations in photonic resonators.